Ablation of Supraventricular Tachycardias From Concealed Left-Sided Nodoventricular and Nodofascicular Accessory Pathways. (May 2020) - Cardona-Guarache, Ricardo; Han, Frederick T.; Nguyen, Duy T.; Chicos, Alexandru B.; Badhwar, Nitish; Knight, Bradley P.; Johnson, Colleen J.; Heaven, David; Scheinman, Melvin M.
Abstract : Background: Nodoventricular and nodofascicular accessory pathways (AP) are uncommon connections between the atrioventricular node and the fascicles or ventricles. Methods: Five patients with nodofascicular or nodoventricular tachycardia were studied. Results: We identified 5 patients with concealed, left-sided nodoventricular (n=4), and nodofascicular (n=1) AP. We proved the participation of AP in tachycardia by delivering His-synchronous premature ventricular contractions that either delayed the subsequent atrial electrogram or terminated the tachycardia (n=3), and by observing an increase in VA interval coincident with left bundle branch block (n=2). The APs were not atrioventricular pathways because the septal VA interval during tachycardia was <70 ms in 3, 1 had spontaneous atrioventricular dissociation, and in 1 the atria were dissociated from the circuit with atrial overdrive pacing. Entrainment from the right ventricle showed ventricular fusion in 4 out of 5 cases. A left-sided origin of the AP was suspected after failed ablation of the right inferior extension of atrioventricular node in 3 cases and by observing a VA increase with left bundle branch block in 2 cases. The nodofascicular and 3 of the nodoventricular AP were successfully ablated from within the proximal coronary sinus (CS) guided by recorded potentials at the roof of the CS, and 1 nodoventricular AP was ablated via a transseptal approach near the CS os. Conclusions: Left-sided nodofascicular and nodoventricular AP appear to connect the ventricles with the CS musculature in the region of the CS os. Mapping and successful ablation sites can be guided by recording potentials within or near the CS os. Abstract : Supplemental Digital Content is available in the text.